Biomedical and Pharmaceutical Applications of Electrochemistry - Djokić, Stojan (Modern Aspects of Electrochemistry, 2016)
This volume of Modern Aspects of Electrochemistry reviews the latest developments in electrochemical science and technology related to biomedical and pharmaceutical applications. In particular, this book discusses electrochemical applications to medical devices, implants, antimicrobially active materials, and drug delivery systems. From reviews of previous volumes: "This long-standing series continues its tradition of offering high quality reviews of established and emerging subject areas, together with the less common aspects of electrochemical science... [and]... deserves a place in electrochemistry libraries and should prove useful to electrochemists and related workers." -Chemistry and Industry "Continues the valuable service that has been rendered by the Modern Aspects series." -Journal of Electroanalytical Chemistry "Will definitely be of much use to researchers in the field of electrochemistry. . . . The editors of this well-produced volume deserve all appreciation for maintaining the excellent standard of the series." -Bulletin of Electrochemistry "Extremely well-referenced and very readable.... Maintains the overall high standards of the series." -Journal of the American Chemical Society.